PENDIDIKAN KHUSUS PEREMPUAN; ANTARA KESETARAAN GENDER DAN ISLAM - Erma Pawitasari (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2018)
Liberalism and gender equity has influenced the society that the different roles between men and women are minimized. Social agreements based on traditions, cultures, and religion are deliberately violated. Women are given opportunity to enter "masculine world", like becoming a president or a soldier. Men are given the opportunity to enter "feminine world", like becoming a women hair stylist or an OBGYN (a doctor that specializes in women's reproductive's health). Special education based on gender is envisaged as discrimative and outdated. Literature research is conducted to understand if special education based on gender is a fruitless idea, if men and women have no unique needs according to their gender differences, and what is Islamic perspective on women education. The finding is an eye-opening. Not only that men and women entail special education to fulfill their different needs, but divergent methods of teaching are also important to boost both male and female students.   Keywords : islamic education, women education, gender education, gender equity, gender